SAT0206 Results of the alterra clinical trial – the efficacy of the alternative dosing regimen for rituximab biosimilar in bdmards naive patients with rheumatoid arthritis. (12th June 2018) - Mazurov, V.; Denisov, L.; Gordeev, I.; Nesmeyanova, O.; Plaksina, T.; Ilivanova, E.; Krechikova, D.; Zonova, E.; Knyazeva, L.; Artemeva, A.; Dokukina, E.; Chernyaeva, E.; et al.
Abstract : Background: Rituximab (RTX) is successfully used in patients with active rheumatoid arthritis (RA) who previously received biological disease-modifying antirheumatic drugs (bDMARDs) at a dose of 1000 mg. Previous preclinical and clinical studies showed that BCD-020 is highly similar to innovator RTX. ALTERRA study demonstrated that first-line use of 600 mg BCD-020 is very effective in bDMARDs naive patients with RA. Objectives: The goal of ALTERRA study was to evaluate the efficacy and safety of the alternative dosing regimen (600 mg) of BCD-020 in bDMARDs naive patients with RA. Methods: ALTERRA study was conducted as multicenter randomized double-blind placebo-controlled phase 3 study. After the screening patients were stratified by age, anti-CCP level and DAS28 score, randomized (2:1) into 2 arms and received BCD-020 (in combination with methotrexate (MTX)) in a dose 600 mg IV or placebo (in combination with MTX) on day 1 and day 15, then, if the activity of arthritis persisted after 24 wks of study, a second course was provided. Patients were observed up to 52 wks. Results: A total of 159 patients were enrolled in ALTERRA study, 107 patients in BCD-020 arm and 52 patients in placebo arm. Efficacy : ACR20 at wk 24 was reached by 65.69% of patients in BCD-020 arm and 29.41% in placebo arm (p=0.00005, the difference in proportion of registration ACR20 with 95%CI was 29.41 [19.27%; 53.28%], margin 10.5%) in per protocol population, so hypothesis of superiority was confirmed. The performed analysis showed a much more pronounced decrease in the DAS28–4 (ESR) index in BCD-020 arm compared with placebo arm (p=0.0006) at wk 24. A much more significant decrease in change of the HAQ-DI index was also shown in the BCD-020 arm (p=0.008). Analysis of efficacy at wk 52 showed the preservation of the response after 2 courses of therapy with BCD-020, 600 mg (in combination with MTX): ACR20 reached by 84.5%, ACR50 – by 54.6%, ACR70 – by 29.9 % of patients. Safety: : BCD-020 showed a favorable safety profile with no significant difference with placebo use (in combination with MTX). After 24 wks patients of both groups developed high similar level of related adverse events: 16.8% of patients in BCD-020 arm and 11.76% in placebo arm (p=0.555). There were only 3 cases of severe adverse events (2.8%) in BCD-020 arm and 2 cases (3.92%) in placebo group. From wk 24 to wk 52: 13.08% of patients (who received 2 courses of BCD-020) and 19.61% of patients (who received one course of BCD-020 after 24 wk) developed related adverse events. Figure 1 ACR 20/50/70 in bDMARDs naive patients with RA after 24-wk treatment of BCD-020/placebo (in combination with MTX). Conclusions: ALTERRA study showed high efficacy and favorable safety profile of RTX biosimilar BCD-020 at a dose of 600 mg in combination with MTX in bDMARDs naive patients with RA. Disclosure of Interest: V. Mazurov: None declared, L. Denisov: None declared, I. Gordeev: None declared, O. Nesmeyanova: None declared, T. Plaksina: None declared, E. Ilivanova: None declared, D. Krechikova: None declared, E. Zonova: None declared, L. Knyazeva: None declared, A. Artemeva Employee of: JSC BIOCAD, E. Dokukina Employee of: JSC BIOCAD, E. Chernyaeva Employee of: JSC BIOCAD, R. Ivanov Employee of: JSC BIOCAD